2018
DOI: 10.1111/bjh.15086
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐ and post‐transplant minimal residual disease predicts relapse occurrence in children with acute lymphoblastic leukaemia

Abstract: Relapse remains the leading cause of treatment failure in children with acute lymphoblastic leukaemia (ALL) undergoing allogeneic haematopoietic stem cell transplantation (HSCT). We retrospectively investigated the prognostic role of minimal residual disease (MRD) before and after HSCT in 119 children transplanted in complete remission (CR). MRD was measured by polymerase chain reaction in bone marrow samples collected pre-HSCT and during the first and third trimesters after HSCT (post-HSCT1 and post-HSCT3). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 52 publications
9
50
0
Order By: Relevance
“…Moreover, we also identified pre‐MRD status as an independent predictor of LFS and OS whereby MRD negative patients showed clear superiority in achieving better LFS and OS compared to the MRD positive ones, either using 0% or 0.01% as cutoff values for positive and negative (Figure and Supporting Information Figure S1). In a recent study from Italy examining the outcomes of 119 transplanted pediatric patients with ALL, consisting of matched sibling donors (38%), matched unrelated donors (49%), and haploidentical donors (13%), positive pre‐MRD was shown to be a potent predictor of both CIR and event‐free survival . In UCBT settings, an analysis on behalf of the Eurocord, Cord Blood Committee and the Acute Leukemia working team of the European group for Blood and Marrow Transplantation showed that, for adult cases with Ph + ALL, 3‐year cumulative incidence of relapse was 45% in MRD + and 16% in MRD − patients ( P = 0.013).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we also identified pre‐MRD status as an independent predictor of LFS and OS whereby MRD negative patients showed clear superiority in achieving better LFS and OS compared to the MRD positive ones, either using 0% or 0.01% as cutoff values for positive and negative (Figure and Supporting Information Figure S1). In a recent study from Italy examining the outcomes of 119 transplanted pediatric patients with ALL, consisting of matched sibling donors (38%), matched unrelated donors (49%), and haploidentical donors (13%), positive pre‐MRD was shown to be a potent predictor of both CIR and event‐free survival . In UCBT settings, an analysis on behalf of the Eurocord, Cord Blood Committee and the Acute Leukemia working team of the European group for Blood and Marrow Transplantation showed that, for adult cases with Ph + ALL, 3‐year cumulative incidence of relapse was 45% in MRD + and 16% in MRD − patients ( P = 0.013).…”
Section: Discussionmentioning
confidence: 99%
“…Such factors cannot be reliably compared in three different retrospective studies, but some differences can be discussed. The HCT indication differed between the studies; in our cohort there were no PhALL cases and the HCT indication at the end of consolidation was MRD ≥10 À3 in the NOPHO versus 5 9 10 À4 in the BFM-Associazione Italiana di Ematologia e Oncologia Pediatrica (AEIOP) protocols in the two studies reported by Lovisa et al (2018) and Sutton et al (2015). Yet, these differences may not play a major role due to the relatively small difference in the MRD cut-off and the fact that PhALL patients are considered a low risk group within very high-risk patients (Pulsipher et al, 2014).…”
Section: Discussionmentioning
confidence: 77%
“…The association between MRD and relapse following HCT is well established in mixed remission cohorts (Knechtli et al , ; Sramkova et al , ; Bader et al , ; Balduzzi et al , ), but very sparse data exist regarding the influence of pre‐HCT MRD in putatively heterogenous CR1 cohorts. Two recent studies analysed the MRD dynamics pre‐ and post‐HCT in a total of 43 and 41 children, respectively, transplanted in CR1 according to national protocols (Sutton et al , ; Lovisa et al , ). In these cohorts, the fraction of MRD negative patients was markedly lower than in our cohort, 47% and 52% respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations